INOVASI MANAJEMEN PENDIDIKAN DI MADRASAH TSANAWIYAH AR ROSIDIYAH BANDUNG - Ahmad Husni Hamim; Ibnu Abdillah Hammam Fauzi; Qiqi Yuliati Zakiah; Mohammad Erihadiana; Asep Munawar (STAI Pelabuhan Ratu, 2021)
This study aims to determine the innovation of education management at MTs Ar Rosidiyyah Bandung. This research is a field research (field work research) which includes aspects of planning, implementation and evaluation. Sources of data in this study were the head of the madrasa, waka curriculum, waka sarpras and several teachers. In collecting data, the author uses three kinds of techniques, namely observation, interviews and documentation. Furthermore, the authors analyzed using the Milles and Huberman interactive analysis model, with the flow of data reduction, data compilation and drawing conclusions. The results of the research show that: Educational management innovation at MTs Ar Rosidiyyah Bandung is carried out with reference to three stages, namely: First, Innovation at the planning stage which includes the goal process, problem identification, supports and barriers, alternative problem solving, alternative decision making, and evaluation. Second, innovation at the implementation stage which includes the process of socialization, polling, and dissemination. Third, innovation at the evaluation stage which includes the process of identifying problems, making problem priority scales, problem analysis, alternative solutions, and follow-up plans